Control de seguimiento de trayectoria y control de velocidad del motor BLDC de un vehículo autónomo a escala-VAE (2024)
The repository contains the data obtained in practice, as well as the codes for trajectory and speed control in C, Python and MATLAB. Additionally, test results and system operation are included.